Place Identity Generated by Facade Color of Urban Building - Maulina, Wilda; Fitria, Tika Ainunnisa; Soewarno, Nurtati (Universitas Muhammadiyah Surakarta, 2024)
Color as a spatial dimension plays an important role in shaping human perception of the identity of a place. The urban public environment is usually characterized by crowds of people and many buildings. The color of the facade on the building which is not well planned makes it even more visually busy. This research aims to explore the identity of a place that can be seen from the color of building facades in urban public environments. The case study in this research is the public area of Jalan dr. Rajiman Surakarta. Even though it looks busy, researchers will try to map the colors of the existing facades by documenting the colors of the facades along Jalan Dr Radjiman from photos. This data is processed using graphic design applications and facade color mapping to find color patterns that lead to the identity of the place. The results of the research are that even though the area has busy building facades, based on the color of the facades, several color templates were found that show similar identities.